Are the economic valuations of marine and coastal ecosystem services supporting policymakers? A systematic review and remaining gaps and challenges - Andrea Mattia Pacifico; Luca Mulazzani; Giulio Malorgio (Frontiers in Marine Science)
With the increasing adoption of the ecosystem approach as integral to sustainable development policies, the economic valuation of marine and coastal ecosystem services (ESs) has become relevant for informing decision-making processes. Through an integrated approach encompassing bibliometric, network, and content analyses, this review is aimed at analyzing the evolution trend, the main research clusters, and the research gaps of the scientific literature in the field of economic valuation of marine and coastal ESs. The bibliometric results showed that the research field is experiencing an evolving positive trend and represents a challenging research topic. From the network and overlay visualization of keyword co-occurrences, it emerged that the research clusters comprehensively address the key policy-relevant issues. In the content analysis, an examination of the estimated ESs and the economic valuation methods used by studies with the highest impact on scientific research was conducted. The findings suggest that while studies provide valuable data and insights, their practical applicability in policymaking is limited, due to contextual relevance and bias issues. Overall, the review underscores the need for a paradigm shift to better inform real-world policy decisions, identifying the Marine Spatial Planning (MSP) process as a key framework for bridging these gaps in future research and policy implementation.